A mística da dança do toré: Imaginário social do povo indígena Tabajara da Paraíba - Figueiredo, Márcia Medeiros (2020)
The general objective of this research was to analyze the Toré dance, within the Tabajara indigenous social imagery from the mystique, considering its symbolic constructions. For that, the imaginary of this present group in the symbols used in the mystic of this dance was investigated, which educates and strengthens the indigenous people. This population, located in the municipality of Conde-PB, in the villages Vitória and Barra de Gramame, experiences an ethnogenesis process, with regard to the recognition of their customs, culture, traditions and ethnic identity. The sacred Toré is a typical dance of struggle and resistance, present in the indigenous cultures of Northeastern Brazil, which seeks resignification and affirmation in each ethnic group. Authors such as Barcellos and Farias (2015); Cavalcanti (2018; 2010); Durand (2002); Eliade (2008; 1992); Grün (2012), among others, are some theorists who anchor this work. This is a research with a qualitative approach, with an ethnographic contribution, whose research instruments are the field diary, participant observation and semi-structured interview. A differential of this study is the photographic record, which directly corroborates in the analysis of images cataloged at the moment of the dance with the researched subjects. The research, at first, describes about the mystical and imaginary Tabajara; in the second stage, the Toré Tabajara dance stands out, about which meanings are brought by the group or individually, about the symbolic imagination found in this practice. From this research it was possible to realize that the Toré has an unimaginable dimension, for the population it is a symbol of struggle, resistance, union, belonging. It is stated how the Toré involves an ancestral dance, of a spiritual and mystical character, presenting ritualistic, archetypal, sacred and mythical aspects. While it is also a political movement, as it represents an immaterial heritage that values indigenous culture. Thus, the Toré dance allows the perpetuation of customs, traditions, respect and the revival of this indigenous Tabajara ethnic group from Paraíba.